2017
DOI: 10.1177/0300985817738096
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Vacuolization in Feline Panleukopenia Virus Infection

Abstract: Feline panleukopenia virus (FPV) infections are typically associated with anorexia, vomiting, diarrhea, neutropenia, and lymphopenia. In cases of late prenatal or early neonatal infections, cerebellar hypoplasia is reported in kittens. In addition, single cases of encephalitis are described. FPV replication was recently identified in neurons, although it is mainly found in cells with high mitotic activity. A female cat, 2 months old, was submitted to necropsy after it died with neurologic deficits. Besides typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 15 publications
5
24
0
Order By: Relevance
“…Interestingly, our results showed no pathological changes suggesting cerebellar hypoplasia in 20 affected cats and dogs, implying that CPPV-1 infection in the brains of cats and dogs might be associated with CNS diseases other than cerebellar hypoplasia. These results support the findings of previous studies that reported CNS manifestation of CPPV-1 in cats and dogs associated with an outcome of neurodegeneration and leukoencephalopathy ( 7 , 8 ). The mechanism that serves the infection of CPPV-1 outside the Purkinje layer of the cerebellum has yet to be elucidated.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, our results showed no pathological changes suggesting cerebellar hypoplasia in 20 affected cats and dogs, implying that CPPV-1 infection in the brains of cats and dogs might be associated with CNS diseases other than cerebellar hypoplasia. These results support the findings of previous studies that reported CNS manifestation of CPPV-1 in cats and dogs associated with an outcome of neurodegeneration and leukoencephalopathy ( 7 , 8 ). The mechanism that serves the infection of CPPV-1 outside the Purkinje layer of the cerebellum has yet to be elucidated.…”
Section: Discussionsupporting
confidence: 92%
“…In utero parvovirus infection is one of the first suspicions in young cats with diffuse and symmetrical cerebellar signs and MRI findings characterised by cerebellar volume reduction, similar to one of the cats in this report, but no spinal involvement has been described and signs are typically non‐progressive 1 27–30…”
Section: Discussionsupporting
confidence: 69%
“…Most of the viruses belonging to the Parvoviridae family replicate in mitotically active cells such as intestinal crypt epithelial cells; however, recent studies demonstrated the presence of parvoviruses in typically nonmitotic cells such as neurons. 11,34,36 Furthermore, the pathogenesis of bocaviruses with respect to tissue tropism and replication is not well documented. In this way, the CBoV-2 infection in these puppies resembled that of CBoV-1, which shows viral inclusion bodies in enterocytes.…”
Section: Discussionmentioning
confidence: 99%